PENGARUH KOMISARIS INDEPENDEN, LEVERAGE, SIZE DAN CAPITAL INTENSITY RATIO PADA TAX AVOIDANCE - Cahyadi Putra, I Gusti Lanang Ngurah Dwi; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
Tax avoidance is tax planning which exploit loopholes contained in the tax laws that are legal. The population in this study are all companies listed on the Indonesia Stock Exchange 2012-2014. Sample selection technique used is to nonprobability sampling method is purposive sampling technique. The number of samples in the study sample was 189 during the third period. Data analysis techniques used in this research is multiple linear regression analysis. The analysis of this study showed an Independent Commissioner and size positive and significant impact on tax avoidance, it means that the higher the number of Independent Commissioners and the higher the size of the company or the size of tax avoidance, the level will be higher. Leverage ratio and capital intensity had no significant effect on tax avoidance, it means that the variable is not a significant influence on the practice of tax evasion.
Keywords: tax avoidance, Independent Commissioner, leverage, size, and capital intensity ratio